The New HR Paradigm: Integrating AI And Human Insight For Superior Talent Management - Laelawati, Kania (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research investigates the impact of AI Integration and Human Insight on Superior Talent Management at PT Aneka Gas Industri, focusing on both direct and indirect effects mediated by HR Practices. Utilizing a quantitative research design with a sample of 70 employees and analyzed through SMART PLS, the study finds that AI Integration has a significant positive effect on both HR Practices and Superior Talent Management, demonstrating its crucial role in enhancing talent management processes. The analysis reveals that the impact of Human Insight on HR Practices is not statistically significant, and its indirect effect on Superior Talent Management is also not significant. These results highlight the critical importance of AI in optimizing HR practices and improving talent management outcomes while suggesting that further exploration is needed to better understand and leverage Human Insight within talent management strategies.